La Biennale del Paesaggio Mediterraneo - Moretti, Francesca (Ri-Vista. Research for landscape architecture, 2015)
The biennial exhibition of Mediterranean Landscape is an opportunity to understand the reasons of the new landscapes, to revise the interpretative models. It’s also a chance to wonder about new ways for sustainable development that could take up the legacy of a millenary civilization. The conference had the fixed aim to compare some contemporary thesis about the concept of landscape and to analyze the Mediterranean area in a historical, social, cultural and political perspective, offering the necessary stuffs for consideration and debate.